Effectiveness of topical application with dexamethasone during sagittal split osteotomy of the mandible in minimising clinical symptoms of postoperative neurosensory disorders - Iryna Logvynenko; Larysa Dakhno; Valeriia Bursova (BMC Surgery)
Abstract Background The aim of this study was to investigate the effectiveness of topical application with dexamethasone during BSSO due to its anti-inflammatory effect and decreasing of postoperative nerve oedema in minimising clinical symptoms of NSD associated with inferior alveolar nerve (IAN) injury in postoperative period, based on the results of sensory diagnostic tests, such as light touch test and its modifications. Methods Through randomisation, 2 groups were selected from 22 patients: the experimental– where topical application with solution of dexamethasone phosphate 0.4% (4 mg/1 ml ampules) during sagittal split osteotomy of the mandible was used, and the control– where the classical technique of BSSO was held. Results Authors performed diagnostics of NSD using Light Touch test on 1st day, 1st week, 1st month, 3rd month and 6th month postoperatively. The experimental group showed improvements in sensory recovery compared to the control group, particularly from 1 week to 3 months post-surgery. By 6 months, both groups achieved similar levels of sensitivity restoration. Conclusions This confirms the effectiveness of proposed method and opens up further prospects for the updated function of the IAN following the BSSO. Clinical trial number Not applicable.